2020
DOI: 10.1016/j.celrep.2020.108006
|View full text |Cite|
|
Sign up to set email alerts
|

Structure in Neural Activity during Observed and Executed Movements Is Shared at the Neural Population Level, Not in Single Neurons

Abstract: Highlights d Neural activity for observed and executed movements occupies a shared subspace d The shared subspace is composed of both congruent and incongruent neurons d Neural dynamics are more similar within the shared subspace than outside it d Observation and execution also have a context-specific exclusive subspace

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 73 publications
(144 reference statements)
4
20
0
1
Order By: Relevance
“…Typically, a mirror neuron fires both when individual acts and when the individual observes the same action performed by another. That is, the mirror neuron is believed to mediate the understanding of others’ behavior ( Jerjian et al, 2020 ; Jiang et al, 2020 ; Pezzulo et al, 2022 ). By contrast, the role of causal inference neurons in our study was putatively participating in self-identification and self-other discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, a mirror neuron fires both when individual acts and when the individual observes the same action performed by another. That is, the mirror neuron is believed to mediate the understanding of others’ behavior ( Jerjian et al, 2020 ; Jiang et al, 2020 ; Pezzulo et al, 2022 ). By contrast, the role of causal inference neurons in our study was putatively participating in self-identification and self-other discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…These findings emphasized the similarity between the neural codes for observed and executed actions, that is, the visual and motor formats. Nonetheless, subsequent studies have shown that MNs in various nodes of the action observation network (AON) (2) can exhibit visual responses to actions performed with tools (3,4), actions implied by moving cues (5)(6)(7)(8)(9)(10), or even withheld actions signaled by an instructive cue (11,12), suggesting a greater flexibility and broader relationship between the visual and motor codes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggests that the shape of the manifold on which neural states lie can reveal important features of the underlying dynamics of the system [ 70 72 , 137 142 ]. We believe the same holds for our data, particularly regarding the difference between the shapes of the decision manifolds in PMd versus M1.…”
Section: Discussionmentioning
confidence: 99%